Acoustic scattering of buried stainless steel spheres: Theoretical analysis and experimental verification. (February 2021) - Li, Xiukun; Wu, Yushuang; Yu, Ge; Zou, Yifei
Abstract: The resonance characteristics of elastic acoustic scattering play an important role for buried target detection and identification. Taking a stainless steel sphere as the target, the acoustic scattering of the target under free-field and buried conditions are calculated using the corresponding COMSOL models. The influences of the burial layer on the Rayleigh wave and Whispering-Gallery wave are analyzed using the partial-wave representation of the form function and the dispersion curve. Compared to the scattering in free-field, the Rayleigh resonance peaks are significantly suppressed under the considered burial layer, while less affecting the Whispering-Gallery resonances. The method of isolation and identification of resonance (MIIR) is used to process the experimental data and hence the elastic resonances in free-field and buried conditions are obtained. The elastic resonances obtained in free-field are mainly Rayleigh resonance peaks, while the Whispering-Gallery resonances are the elastic characteristics under the buried condition. Moreover, using the fitting analysis of the two types of resonances, the calculated expressions for the target radius estimation under the two conditions are obtained, and verified from experimental results.